The mobile learning technique for measuring internal intensity in recreational basketball - Sánchez-Lima, Alejandro; Pérez-Toledano, Miguel Ángel; Villafaina, Santos; García-Ceberino, Juan Manuel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
Coaches seek to identify the task constraints that compel players to exert greater effort to enhance performance. This empirical, cross-sectional study, conducted using a single-case manipulative strategy, compared the internal intensities elicited by different tasks (i.e., 1 vs. 1, 2 vs. 2, 3 vs. 3, 4 vs. 4, and 5 vs. 5) in recreational basketball using a mobile learning technique during a session of increasing complexity. In addition, perceived effort was analysed. It involved 59 players (34 boys and 25 girls; mean age = 14.61±1.78 years) from a public institution in the southwest of Spain. Intensities measured included heart rate, monitored via smartphones, and perceived effort, assessed using a pictorial-curvilinear scale. The correlation between both measures of intensities was calculated using Pearson's correlation, revealing positive correlations in the training tasks (p<0.05). Tukey's post hoc test revealed no statistically significant differences (p>0.05) in heart rate between the 3vs.3 in ½ court and 4vs.4 with space repetition compared to the 5vs.5 game. Both tasks should be incorporated in training as they elicited physiological demands similar to those in a competition situation.